Effects of global versus local trunk muscle strength training on muscle strength, proxies of power and rowing-specific performance in pubertal male rowers - Raouf Hammami; Yassine Negra; Abdelkader Mahmoudi; Walid Selmi; Haithem Rebai; David G. Behm; Anis Chaouachi; Urs Granacher (PLoS ONE, 2026)
Strength training is fundamental during long-term athlete development to enhance strength and power supporting sport-specific performance. In rowing, trunk muscles stabilize the body and transmit forces between the lower and upper limbs. This study compared the effects of pre-season global (GST) versus local (LST) trunk strength training on muscle strength, power, and rowing-specific performance in young male rowers. Twenty-eight Tier 2 athletes aged 12–13 years (circa-PHV = 0.2–0.3) completed a 6-week program with two weekly sessions. GST involved machine-based and free-weight trunk exercises at 70% 1-RM, whereas LST emphasized body-weight trunk exercises on stable and unstable surfaces. Pre- and post-tests included lower- and upper-limb power, trunk strength, and a 700-m rowing ergometer test. Significant group-by-time interactions were found for all strength (d = 3.04–3.84; p < 0.001), power (d = 0.75–2.34; p < 0.01), and rowing performance outcomes (d = 1.61; p < 0.001). Post-hoc analyses indicated greater improvements in GST (d = 0.28–1.87; p < 0.001) than in LST (d = 0.11–0.73; p < 0.001). In conclusion, GST produced larger performance gains than LST. However, these effects likely reflect the combined influence of exercise modality and higher external loading intensity, rather than trunk muscle recruitment patterns alone. These findings should be interpreted with caution given that differences in external loading between conditions (70% 1-RM vs. athletes’ body mass) confound the comparison of GST versus LST modalities. Strength and conditioning specialists may consider incorporating GST to enhance foundational strength and power in pubertal male rowers, but further research controlling for training load is needed to isolate the effects of exercise modality.